Formulating Paper Soap with Coconut and Olive Oils: A Natural Solution for On-the-Go Hygiene - Emma Emawati; Siti Aisyah Aprilia; Anne Yuliantini (PT CENDEKIA SCIENCE AND TECHNOLOGY, 2025)
Paper soap served as a practical alternative for hand hygiene, especially for individuals with high mobility who required portable, lightweight, and hygienically stored products. This study aimed to formulate handwashing paper soap using a combination of coconut and olive oils, with potassium hydroxide (KOH) as the saponification agent, and to evaluate its quality based on the Indonesian National Standard (SNI) No. 2588:2017 for liquid hand soap. A laboratory-based pure experimental method was used to determine the optimal combination of ingredients. The soap base formulation that showed the most favorable characteristics consisted of coconut oil and olive oil mixed in equal proportions, with KOH as the alkali. This combination produced a liquid soap with good cleansing ability, softness, and skin moisture retention. The evaluation results showed that the final formulation met all quality parameters: a pH value of 9.37, foam height of 10.5 cm, and free fatty acid content of 0.985%. Among the two types of paper tested, dry cotton tissue proved to be the most suitable medium for soap application due to its excellent absorbency and even drying. Panelist testing further confirmed the acceptability of the product. Most respondents reported positive impressions regarding the product’s texture, foaming properties, and skin feel after use. The paper soap did not cause irritation or a burning sensation, and it was easy to use and dispose of, increasing its appeal for daily use and travel. In conclusion, the formulation successfully produced a functional and user-accepted paper soap that met national quality standards. The study demonstrated that natural ingredients could be effectively used to develop innovative hygiene solutions that are both practical and safe for everyday use.